EFFECTIVENESS OF COMPLEX TREATMENT OF CHRONIC PERIODONTITIS IN PATIENTS WITH ORTHODONTIC STRUCTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article is devoted to the analysis of the effectiveness of complex treatment of periodontal diseases in patients using orthodontic devices. The study covers patients with various degrees of periodontal pathology undergoing treatment. In the course of the work, methods of professional hygiene, antiseptic therapy and individual monitoring were used. The results showed a significant improvement in clinical indicators, such as a decrease in the depth of pockets and a decrease in inflammatory processes in the gum area. The work emphasizes the importance of a multidisciplinary approach to the treatment of patients with orthodontic structures.